Applying TSSL in database schema modeling: Visualizing the syntax of gradual transitions - Adi Katz (OmniaScience, 2018)
Since database conceptual modeling is a complex cognitive activity, finding an appropriate pedagogy to deliver the topic to novice database designers is a challenge for Information Systems (IS) educators. The four-level TSSL model that is known in the area of human-computer interactions (HCI) is used to explain and demonstrate how instructional design can minimize extraneous cognitive load in the conceptual modeling task of designing a database schema. The instructional design approach puts focus on the syntactic level of TSSL, to explain how visualizing gradual transitions between hierarchic levels of the schema is effective in database modeling. The current work demonstrates the approach, and at the next phase we plan to experimentally test the effectiveness of the approach by comparing performance and attitudes of students who are exposed to emphasizing the syntax of the gradual transitions in schema structure to those who are not exposed to it.